The brute [videorecording (DVD)] = El bruto - Buñuel, Luis, 1900-1983; Armendáriz, Pedro, 1912-1963; Jurado, Katy; Arenas, Rosita, 1933-; Soler, Andrés (Facets, 2019)
A slow-witted but strong slaughterhouse worker who is hired by a slumlord to break a tenant strike accidentally kills one of the strike leaders. He is then drawn into a doomed affair with the landlord's wife.